2016
DOI: 10.4238/gmr.15028043
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, identification, and degradation performance of a PFOA-degrading strain

Abstract: ABSTRACT. The perfluorooctanoic acid (PFOA)-degrading strain YAB1 was isolated from the soil near a perfluorinated compound production plant through acclimation and enrichment culture, using PFOA as the sole carbon source. This strain was preliminarily identified as Pseudomonas parafulva based on colony morphology, physiological and biochemical features, and 16S rRNA gene sequencing. Using shaking flask fermentation, the maximum tolerable concentration of YAB1 on PFOA was found to be 1000 mg/L. The optimal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(47 citation statements)
references
References 20 publications
0
34
0
Order By: Relevance
“…For instance, Pasquini et al (2013) discovered that E. coli was not able to biodegrade PFOS and PFOA. In contrast, P. plecoglossicida (Chetverikov et al, 2017), P. parafulva (Yi et al, 2016), This study demonstrated that biodegradation was possible, although this only involved the breakdown of the non-fluorinated moiety. However, to our knowledge, no field or in situ experiments have been conducted on PFC biodegradation.…”
Section: Bioremediationmentioning
confidence: 71%
“…For instance, Pasquini et al (2013) discovered that E. coli was not able to biodegrade PFOS and PFOA. In contrast, P. plecoglossicida (Chetverikov et al, 2017), P. parafulva (Yi et al, 2016), This study demonstrated that biodegradation was possible, although this only involved the breakdown of the non-fluorinated moiety. However, to our knowledge, no field or in situ experiments have been conducted on PFC biodegradation.…”
Section: Bioremediationmentioning
confidence: 71%
“…D2, exploiting glucose and/or acetate as the only source of carbon and energy, partially degraded PFOS, highlighting that even non-related carbon substrates can elicit cometabolic reactions [33]. Other investigations unveiled that PFOA and PFOS can be decomposed by pure bacterial cultures of P. parafulva, P. aeruginosa, or P. plecoglossicida, being the latter capable of utilizing PFOS as carbon source biotransforming it in perfluoroheptanoic acid with the release of fluorine ions [54][55][56]. Further, Huang and Jaffé (2019) reported on the ability of Acidimicrobium sp.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the Indigenous bacterial species isolated from PFAS-contaminated environments have shown the ability to remediate PFAS compounds; two strains of Pseudomonas (PS27 and PDMF10) were able to remove 32 and 28% of PFAS compounds, respectively, within 10 days of incubation under alkanotrophic conditions (Presentato et al, 2020). Further, a decrease of around 32% in PFAS was also reported during a 96 h incubation of Pseudomonas parafulva (Yi et al, 2016) along with a 67% decrease in PFAS concentration over 48 h incubation of Pseudomonas aeruginosa (Kwon et al, 2014). In another study, Pseudomonas plecoglossicida utilized PFAS as an energy source, producing perfluoroheptanoic acid and releasing fluorine ions as a result (Chetverikov et al, 2017).…”
Section: Bioremediation Optionsmentioning
confidence: 85%